Study of DNA damage induced by dental bleaching agents in vitro Estudo de danos no DNA induzidos por agentes clareadores dentais in vitro - Daniel Araki Ribeiro; Mariângela Esther Alencar Marques; Daisy Maria Fávero Salvadori (Sociedade Brasileira de Pesquisa Odontológica, 2006)
Dental bleaching is a simple and conservative procedure for aesthetic restoration of vital and non-vital discolored teeth. Nevertheless, a number of studies have demonstrated the risk of tissue damage from the contact of these agents with the oral mucosa. In the current study, the genotoxic potential associated with exposure to dental bleaching agents was assessed by the single cell gel (comet) assay in vitro. Chinese hamster ovary (CHO) cells in vitro were exposed to six commercial dental bleaching agents (Clarigel Gold - Dentsply; Whitespeed - Discus Dental; Nite White - Discus Dental; Magic Bleaching - Vigodent; Whiteness HP - FGM and Lase Peroxide - DMC). The results pointed out that all dental bleaching agents tested contributed to DNA damage as depicted by the mean tail moment, being the strongest effect observed with the highest dose of hydrogen peroxide (Whiteness HP and Lase Peroxide, at a 35% concentration). On the other hand, Magic Bleaching (Vigodent) induced the lowest level of DNA breakage. Negative and positive controls displayed absence and presence of DNA-damaging, respectively. Taken together, these results suggest that dental bleaching agents may be a factor that increases the level of DNA damage. A higher concentration of hydrogen peroxide produced higher noxious activities in the genome as detected by single cell gel (comet) assay. Clareamento dental é um procedimento simples e conservador para restaurar esteticamente a cor de dentes vitais e não-vitais. Entretanto, alguns estudos têm demonstrado o risco de dano tecidual a partir do contato desses agentes com a mucosa bucal. Neste presente estudo, o potencial genotóxico associado à exposição aos agentes clareadores dentais foi avaliado pelo teste de células individualizadas em gel (teste do cometa) in vitro. Células de ovário de hamster chinês (CHO) in vitro foram expostas a seis agentes clareadores dentais comercialmente disponíveis (Clarigel Gold - Dentsply; Whitespeed - Discus Dental; Nite White - Discus Dental; Magic Bleaching - Vigodent; Whiteness HP - FGM e Lase Peroxide - DMC). Os resultados mostraram que todos os agentes clareadores testados contribuíram para os danos no DNA, como demonstrado pela média do momento da cauda, sendo o efeito mais forte observado na mais alta dose de peróxido de hidrogênio (Whiteness HP e Lase Peroxide, na concentração de 35%). Por outro lado, Magic Bleaching (Vigodent) induziu o menor nível de quebras no DNA. Os controles negativo e positivo apresentaram ausência e presença de danos no DNA, respectivamente. Em suma, esses resultados sugerem que os agentes clareadores dentais podem ser um fator que aumenta o nível de danos no DNA. Uma concentração de peróxido de hidrogênio mais elevada produziu atividades nocivas mais severas no genoma como detectado pelo teste do cometa.